Battery aware hybrid forwarding scheme for 6lowpan - Farhad, Mesrinejad (2012)
This thesis mainly focuses on fragments forwarding of 6LoWPAN through adaptation layer since the fragmentation and header compression, the main responsibilities of the adaptation layer, are necessary to fit the IPv6 packets with the sensor nodes. Proposed energy model considers the data payload size and the header size of different layers to evaluate the energy consumption and lifetime of network before and after fragmentation and header compression. Likewise, an analysis of simulation based scenario is carried out to investigate the effect of fragmentation on energy consumption. In order to improve the functionalities of adaptation layer,battery level of each node located at the first level of sensor network -the nodes that can directly communicate with the gateway- is used as a primary parameter to manage data forwarding between 6LoWPAN gateway and the sensors at the first level. Furthermore, two existing forwarding schemes namely route-over and mesh-under are evaluated. Based on evaluation in this thesis, route-over and mesh-under suffers from high end-to-end delay and energy consumption respectively. Therefore, 6LoWPAN requires a more efficient forwarding scheme in terms of energy consumption and delay. In this research, Hybrid Forwarding Scheme (HFS) is proposed which exploits the features of route-over and mesh-under. In HFS, all fragments of each packet are sent to the same destination. Intermediate nodes, in addition to forward the fragments to the next hop, check the lost fragments and request from the previous hop. Reassembling process will be done at the final destination. The proposed method reduces the delay, decreases energy consumption especially when there is retransmission, and increases the lifetime of network. The research data in this thesis is drawn from two main sources: mathematical model and QualNet simulator. Based on the obtained results, the fragmentation increases the energy consumption from 57.8 to 69.8 percent. Higher energy consumption reduces the lifetime of the networks; accordingly the lifetime is reduced from 7.7% to 38.5%. Thus, the number of alive nodes especially at the first level is decreased during the simulation time. By using the battery level as a decision parameter to deliver fragments to the next hop, the lifetime is increased from 6.9 to 20.9 percent. Furthermore, the number of alive nodes is also a parameter which is improved during the simulation time. HFS reduces delay about four times compared to the route-over and from 20.3 to 29.8 percent compared to the mesh-under scheme. Hybrid forwarding scheme also decreases energy consumption from 18.1 to 35.1 percent compared to the route-over scheme and 50.68 to 58.43 percent compared to the mesh-under. Finally, by combining two methods (using battery level and HFS), the improvements are of lifetime from 17 to 19.22 percent, energy consumption from 25.57 to 26.3, and delay from 1 to 6.44 percent.